Lung and Intestine: A Specific Link in an Ulcerative Colitis Rat Model - Yuan Liu; Xin-Yue Wang; Xue Yang; Shan Jing; Li Zhu; Si-Hua Gao (Gastroenterology Research and Practice)
Background. To investigate the link and mechanisms between intestine and lung in the ulcerative colitis (UC) rat model. Materials and Methods. We used the UC rat model by immunological sensitization combined with local 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) in 50% ethanol enema, observed dynamically animal general state and body weight, examined the histological and functional changes in the colon, lung, liver, and kidney tissues, and detected microvascular endothelium response towards inflammation characterized with the expression of iNOS, TXB2, P-selectin, ICAM-1, and vascular endothelial growth factor A (VEGF-A) in the colon and lung tissue. Results. Pulmonary function results suggested ventilator disorder, and pathological findings showed interstitial pneumonia. There were no significant changes in the liver and kidney function and histopathology. The colon and lung tissue iNOS, TXB2, P-selectin, ICAM-1, and VEGF-A expression of the model rats was significantly higher than the normal rats at both time points. Conclusions. Our study is the first to demonstrate the close association between the large intestine and lung in the immune-TNBS-ethanol-induced UC rat model. Different organs and tissues with the same embryonic origin may share the same pathological specificities in a disease. The present study provided a new way of thinking for pathological changes in clinical complex diseases manifested with multiorgan damage.